1998
DOI: 10.1086/517471
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 as a Potential Sexually Transmitted Agent in Honduras

Abstract: The seroprevalence of human herpesvirus 8 (HHV-8) was studied in 326 human immunodeficiency virus (HIV)-positive and -negative persons from Honduras; women constituted 77% (n = 251) of the subjects. Sera were tested for lytic HHV-8 antibodies by an IFA, and positive samples were confirmed by a radioimmunoprecipitation assay. Of the 326 persons tested, 58 (17.8%) had HHV-8 antibodies. Among the HIV-infected women, 22.7% were seropositive; 11.3% of the HIV-negative women were seropositive. HHV-8 seroprevalence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Complete data from the 326 participants have been already published elsewhere (Sosa et al 1998, Renjifo et al 1999. For purposes of our study, we present data on the 133 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete data from the 326 participants have been already published elsewhere (Sosa et al 1998, Renjifo et al 1999. For purposes of our study, we present data on the 133 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Between March and November 1996, a total of 326 HIV seropositive individuals from all those attending public clinics that belong to the Ministry of Health were deliberatedly recruited for a study by the University of Miami investigating HIV subtypes and human herpesvirus 8 infections (Sosa et al 1998, Renjifo et al 1999). Participants represented a cross-sectional sampling of the population and were recruited, when eligible, as they visited the clinic during their routine medical check up.…”
Section: Population and Methodologymentioning
confidence: 99%
“…Likewise, only 5/ 169 (3%) of HIV negative patients from Honduras were found to be HHV-8 positive when using a cutoff point of 1:40 40 .…”
Section: Epidemiology Of Hhv-8 Infection -Serological Datamentioning
confidence: 96%
“…Almost all of the studies on semen samples reveal either a very low number of HHV-8 positive samples (0 to 33%) regardless of the KS or HIV status of the patients or the absence of HHV-8 DNA (124,129,202,271,280). A study (271) of female commercial sex workers in Honduras found that those positive for HIV had an HHV-8 seroprevalence rate four times as high as those that were HIV negative (36% versus 10%). Martin et al (186), in a multicenter cohort study, found a correlation between HHV-8 infection and the number of male homosexual partners a man had.…”
Section: Sexual Transmissionmentioning
confidence: 99%